8-Bromo-3,4-dihydro-2H-1,3-thiazino[2,3:2 `,1 `]imidazo[5 `,4 `-b]pyridine - Ghacham, H.B.; Rodi, Y.K.; Capet, F.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The imidazopyridine ring system in the title compound, C(9)H(8)BrN(3)S, is almost planar [r.m.s. deviation of the C and N atoms = 0.007 (1) angstrom]. The S and methylene C atoms connected to the five-membered ring lie within this plane. The remaining two methylene groups of the thiazine ring are disordered over two sets of sites in a 0.817 (5): 0.183 (5) ratio.